2007
DOI: 10.1074/jbc.m608025200
|View full text |Cite
|
Sign up to set email alerts
|

The Histone Chaperone Anti-silencing Function 1 Stimulates the Acetylation of Newly Synthesized Histone H3 in S-phase

Abstract: Anti-silencing function 1 (Asf1) is a highly conserved chaperone of histones H3/H4 that assembles or disassembles chromatin during transcription, replication, and repair. We have found that budding yeast lacking Asf1 has greatly reduced levels of histone H3 acetylated at lysine 9. Lysine 9 is acetylated on newly synthesized budding yeast histone H3 prior to its assembly onto newly replicated DNA. Accordingly, we found that the vast majority of H3 Lys-9 acetylation peaked in S-phase, and this S-phase peak of H3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
78
1
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(84 citation statements)
references
References 36 publications
3
78
1
2
Order By: Relevance
“…The histone chaperone Asf1 is required for the acetylation of H3K56, whereas the effect of Asf1 deletion TS4_compacted morula TS4_inner cell mass Theiler_stage_4 TS4_embryo TS4_second polar body TS4_zona pellucida Theiler_stage_5 TS5_inner cell mass TS4_extraembryonic TS5_embryo TS3_zona pellucida Theiler_stage_3 TS3_second polar body TS3_4-8 on other histone acetylation sites is relatively minor as determined by Western blots and MS (18,36,37). Using Western blots, we found that knockdown of Asf1a with shAsf1a in mouse E14Tg2a cells decreases H3K56ac significantly but has very little effect on other acetylation sites in histone H3 (Fig.…”
Section: Decreased H3k56ac Promotes the Loss Of Pluripotency Of Mousementioning
confidence: 99%
“…The histone chaperone Asf1 is required for the acetylation of H3K56, whereas the effect of Asf1 deletion TS4_compacted morula TS4_inner cell mass Theiler_stage_4 TS4_embryo TS4_second polar body TS4_zona pellucida Theiler_stage_5 TS5_inner cell mass TS4_extraembryonic TS5_embryo TS3_zona pellucida Theiler_stage_3 TS3_second polar body TS3_4-8 on other histone acetylation sites is relatively minor as determined by Western blots and MS (18,36,37). Using Western blots, we found that knockdown of Asf1a with shAsf1a in mouse E14Tg2a cells decreases H3K56ac significantly but has very little effect on other acetylation sites in histone H3 (Fig.…”
Section: Decreased H3k56ac Promotes the Loss Of Pluripotency Of Mousementioning
confidence: 99%
“…H3 K56R), rtt109⌬ mutants display sensitivity to replicate stress (18,19,21). Interestingly, loss of the H3/H4 histone chaperone ASF1 also results in the absence of H3 Lys-56-Ac (13,16,18,19,21,22). Taken together, these data suggest an intimate, but poorly understood, functional relationship between Rtt109, Asf1, and H3 Lys-56-Ac.…”
mentioning
confidence: 91%
“…Rtt109, with the histone chaperone Asf1 (anti-silencing function 1), acetylates lysine 56 (Lys-56) on the histone H3 core domain (12,14,15,19). Asf1 is thought to form a transient complex with Rtt109 and stimulate activity by properly presenting H3-H4 dimers for Lys-56 acetylation (23)(24)(25)(26)(27). This mark occurs on newly synthesized H3 in Saccharomyces cerevisiae and Schizosaccharomyces pombe during S-phase and is required for the assembly of H3-H4 dimers onto DNA during cell replication (12,15,28).…”
mentioning
confidence: 99%